Beyond Anthropocentrism: A Comparative Ecotheological Framework of Khalīfah fīl-Arḍ and Imago Dei toward Theo-Ecocentrism - Tonny Andrian Stefanus; David Ming (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2026)
The modern ecological crisis is fundamentally driven by anthropocentric paradigms that exploit the biosphere. Addressing this challenge, this study utilizes the theological frameworks of Khalīfah fīl-Arḍ in Islam and Imago Dei in Christianity as its central units of analysis to construct an applicable interfaith environmental ethics model. Employing a qualitative, comparative theological-philosophical approach through library research, this study systematically analyzes classical and contemporary Qur'anic exegeses, biblical texts, and official church documents. The analysis reveals a vital conceptual intersection: both Abrahamic traditions strictly deconstruct despotic anthropocentrism by redefining human authority not as absolute ownership, but as derivative, accountable stewardship (amanah). The core novelty of this research lies in its transition from passive, compartmentalized dogmatic comparisons to an integrated